(untitled) (Delta Medical College Journal, 2017)
Background: Women with postmenopausal bleeding (PMB) should be thoroughly evaluated. A thorough examination may help in the diagnosis of vulval, vaginal, cervical or pelvic pathology. Objective: This study was carried out to find the probable causes in patients presenting with postmenopausal bleeding. Materials and method: This observational study included 50 women with postmenopausal bleeding and was conducted in the department of Obstetrics and Gynaecology of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorder (BIRDEM) Hospital, Dhaka, Bangladesh, from January 2004 to December 2004. Transvaginal ultrasonogram (TVS), diagnostic curettage and cervical biopsy were done and histopathology report was collected. Results: The mean age of the patients was 57.74 years (range 48-75 years), and the median age of menopause was 50 years. Among the patients 18 (36%) had only diabetes and 25 (50%) patients had both diabetes and hypertension. Nineteen patients (38%) were overweight, 5 patients (10%) were obese and 2 (4%) were morbidly obese. Per speculum examination revealed suspected cervical carcinoma in 5 cases (10%) and cervical polyp in 1 case (2%). The most common clinical finding was atrophy of the uterus and vagina in 26 patients (52%). TVS revealed endometrial thickness of 5mm or more in 17 cases (37.7%) and < 5mm in 26 cases (57.7%). Nine patients (18%) had carcinoma, 16 patients (32%) had benign pathology and 19 (38%) patients had endometrial atrophy on histology. Conclusion: A detailed history taking, thorough physical examination and relevant investigations can lead to a correct detection of cause of postmenopausal bleeding. Those who have normal adnexae and thin endometrium (endometrium <5mm) may not need endometrial biopsy. Delta Med Col J. Jul 2017 5(2): 83-88